Doppler Echocardiography Assessment of Coronary Microvascular Function in Patients With Angina and No Obstructive Coronary Artery Disease - Schroder, Jakob; Prescott, Eva (Frontiers in Cardiovascular Medicine, 2021)
Echocardiographic evaluation is an essential part of the diagnostic work-up in patients with known or suspected cardiovascular disease. Transthoracic Doppler echocardiography (TTDE) enables straightforward and reliable visualization of flow in the left anterior descending artery, and in the absence of obstructive coronary artery disease low TTDE-derived coronary flow velocity reserve (CFVR) is considered a marker of coronary microvascular dysfunction (CMD). TTDE CFVR is free from ionizing radiation and widely available, utilizing high frequency transducers, pharmacologic vasodilator stress and pulsed-wave Doppler quantification of diastolic peak flow velocities. ESC guidelines recommend TTDE CFVR evaluation only following preceding anatomic invasive or non-invasive coronary imaging excluding obstructive CAD. Accordingly, clinical use of TTDE CFVR is limited and CMD frequently goes undiagnosed. An evolving body of evidence underlines that low CFVR is an important and robust predictor of adverse prognosis and continuing symptoms in angina patients both with and without obstructive CAD. The majority of angina patients have no obstructive CAD, particularly among women. This has led to the suggestion that there may be a gender-specific female atherosclerotic phenotype with less epicardial obstruction, and a low CFVR signifying CMD instead. Nevertheless, available evidence indicates low CFVR is an equally important prognostic marker in both men and women. In this review TTDE CFVR is evaluated regarding indication, practical and technical aspects and interpretation of results. Association with symptoms and prognosis, comparison with alternative invasive and non-invasive imaging modalities and possible interventions in angina patients with low CFVR are discussed, and key research questions are proposed.